2021
DOI: 10.3389/fspas.2020.617792
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir Turbulence in the Auroral Ionosphere: Origins and Effects

Abstract: Theory and observations of Langmuir waves and turbulence induced in the auroral ionosphere by electron beams of magnetospheric-origin are reviewed. The theoretical discussions include a brief description of the electrostatic dispersion relation, excitation of Langmuir waves by electron beams, and the stability of beam distributions. The theory of Langmuir turbulence—including the parametric decay instability and wave collapse—is also briefly discussed. The main focus of the review, however, is on the observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 192 publications
0
5
0
Order By: Relevance
“…
Alfvén waves are fundamental features of magnetized plasmas and participate in various processes on different temporal and spatial scales. In the Earth's high-latitude ionosphere, for example, they induce, via electron acceleration, a range of intriguing micro-scale plasma processes involving high-frequency waves (e.g., Akbari et al, 2012Akbari et al, , 2020; they are thought to be responsible for the generation of fine-scale features of auroral arcs (e.g., Semeter et al, 2008); and, on larger scales, are an important component of magnetosphere-ionosphere interactions (e.g., Verkhoglyadova et al, 2018). By accelerating magnetospheric electrons (Chaston et al, 2002;Kletzing & Hu, 2001), heating ionospheric ions, and by carrying field-aligned currents and Poynting flux, Alfvén waves facilitate the exchange of mass, momentum, and energy between the ionosphere and the magnetosphere.
…”
mentioning
confidence: 99%
“…
Alfvén waves are fundamental features of magnetized plasmas and participate in various processes on different temporal and spatial scales. In the Earth's high-latitude ionosphere, for example, they induce, via electron acceleration, a range of intriguing micro-scale plasma processes involving high-frequency waves (e.g., Akbari et al, 2012Akbari et al, , 2020; they are thought to be responsible for the generation of fine-scale features of auroral arcs (e.g., Semeter et al, 2008); and, on larger scales, are an important component of magnetosphere-ionosphere interactions (e.g., Verkhoglyadova et al, 2018). By accelerating magnetospheric electrons (Chaston et al, 2002;Kletzing & Hu, 2001), heating ionospheric ions, and by carrying field-aligned currents and Poynting flux, Alfvén waves facilitate the exchange of mass, momentum, and energy between the ionosphere and the magnetosphere.
…”
mentioning
confidence: 99%
“…Cairn's et al [28], suggested a plasma system composed of nonthermal electrons with an abundance of energetic particles and cold ions to explain the density depletion observed by onboard instruments of the Freja and Viking satellites [29]. To explain the findings made by the Freja satellite, Cairn's et al, [30] proposed a nonthermal electron distribution with an abundance of energetic particles. The nonthermal distribution function for the electron is calculated as suggested by Cairn's et al [31].…”
Section: Introductionmentioning
confidence: 99%
“…Turbulence has been observed in many natural systems with unique dissipation mechanisms, for instance, surface gravity waves [30], capillary waves on a liquid surface [31,32], quantum turbulence in two-fluid regime [33], nearwall turbulence [34], turbulence near the solar nebula [35], or solar wind turbulence [36], magnetohydrodynamics turbulence in partially ionized gas of the interstellar medium [37,38] or with snowdrift where snow particles damp the turbulence in the atmosphere [39], and even auroral ionospheric turbulence [40].…”
Section: Introductionmentioning
confidence: 99%